A national survey of transition from pediatric to adult healthcare providers for adolescents and young adults with type 1 diabetes: perspectives of pediatric endocrinologists in Korea - Jae Hyun Kim; Jae-Ho Yoo (Korean Society of Pediatric Endocrinology, 2021)
Purpose Transition from pediatric to adult healthcare for adolescents and young adults with type 1 diabetes (T1D) increases the risk for poor outcomes. This study aimed to describe the circumstances and clinical practice patterns associated with this transition of care based on a nationwide survey of pediatric endocrinologists in Korea. Methods An electronic survey regarding the healthcare transition of T1D patients was administered to 143 pediatric endocrinologists registered in the Korean Society of Pediatric Endocrinology. Results The response rate was 50.2% (n=72). Among responders, 58.3% (n=42) were females, and 70.8% (n=51) worked in academic medical centers. The main reasons for transfer to adult care were request from a patient or family (69.6%) and age ≥18 years (42.0%). Impediments to transition were a long-lasting therapeutic relationship (72.9%) and lack of adult specialists in T1D care (62.9%). Communication between pediatric and adult endocrinologists was via nonstructured patient summary (68.6%) and telephone or email (27.1%). Responders reported that successful transition requires development of transition protocols (79.2%) and a multidisciplinary team approach for transition care (52.8%). Conclusions Transition care of T1D patients is a challenge to pediatric endocrinologists in Korea. Development of transition care protocols for healthcare providers and improvement of diabetes self-management skills for patients are needed.